Enhancing Corporate Governance: the role of female directors in management accounting and control - Borges, F.; Azevedo, G.; Maria C Tavares; Oliveira, J. (Cisti 2025 - 20th Iberian Conference on Information Systems and Technologies, 2025)
Grounded on agency theory and resource dependency theory this article looks at the role of female directors in strengthening management accounting and management control within corporate governance. Findings show that female directors bring unique skills and perspectives that support conservative financial strategies, improve financial reporting and internal control mechanisms. They create a culture of ethical governance and transparency which is key to sustainable financial performance and stakeholder trust. The results show the value of gender diverse boards in creating robust governance structures that align financial and non financial performance metrics. They also highlight the need for policies that promote gender diversity to achieve more resilient management accounting systems.